2018
DOI: 10.1101/440321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A confirmation bias in perceptual decision-making due to hierarchical approximate inference

Abstract: 1Human decisions are known to be systematically biased. A prominent example of such a bias 2 occurs when integrating a sequence of sensory evidence over time. Previous empirical studies di↵er 3 in the nature of the bias they observe, ranging from favoring early evidence (primacy), to favoring 4 late evidence (recency). Here, we present a unifying framework that explains these biases and 5 makes novel psychophysical and neurophysiological predictions. By explicitly modeling both the 6 approximate and the hierar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…Some studies found stronger weighting of early evidence ("primacy"; 6-9), others stronger weighting of late evidence ("recency"; [10][11][12], and yet others even nonmonotonic weighting profiles (13,14). These distinct temporal weighting profiles may inform about differences in the mechanisms underlying decision formation (14)(15)(16)(17). Yet, mechanistic inferences are limited by the fact that most of the above studies were conducted in different subjects and used various different stimuli and tasks (with evidence varying on different timescales).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found stronger weighting of early evidence ("primacy"; 6-9), others stronger weighting of late evidence ("recency"; [10][11][12], and yet others even nonmonotonic weighting profiles (13,14). These distinct temporal weighting profiles may inform about differences in the mechanisms underlying decision formation (14)(15)(16)(17). Yet, mechanistic inferences are limited by the fact that most of the above studies were conducted in different subjects and used various different stimuli and tasks (with evidence varying on different timescales).…”
Section: Introductionmentioning
confidence: 99%
“…The context dependent noise correlations that speed learning (figure 7), however, would not arise through simple Hebbian learning. Such correlations could potentially be produced through selective topdown signals from the choice neurons, as has been previously proposed (Wimmer et al, 2015;Haefner et al, 2016;Bondy et al, 2018;Lange et al, 2018). Moreover, top-down input may selectively target neuronal ensembles produced through Hebbian learning (Collins and Frank, 2013).…”
Section: Origins Of Useful Noise Correlationsmentioning
confidence: 81%
“…In particular, noise reduction in task irrelevant dimensions might be considered in the same light that is often cast on suppression of task irrelevant dimensions by attentional mechanisms (Zanto and Gazzaley, 2009), in particular for purposes of accurate credit assignment (Akaishi et al, 2016;Leong et al, 2017). One possibility is that compressed low-dimensional task representations in higherorder decision regions (Mack et al, 2019) may pass accumulated decision related information back to sensory regions in order to approximate Bayesian inference (Haefner et al, 2016;Bondy et al, 2018;Lange et al, 2018). As task relevant features are learned, such a process would promote noise correlations between neurons coding those relevant features.…”
Section: Relation To Attentional Effects On Noise Correlationsmentioning
confidence: 99%
“…Recently, two studies have proposed alternative models that can explain the differences of PK time-courses found across subjects and experiments. In the first model, based on approximate Bayesian inference, the primacy effect produced by bottom-up vs. top-down hierarchical dynamics, was modulated by the stimulus properties which could yield different PK time-courses, a prediction that was tested in a visual discrimination task 41 . The second study proposed a model that can produce different PK time-courses by adjusting the time scales of a divisive normalization mechanism, which yields primacy, and a leak mechanism, which promotes recency 42 .…”
Section: Discussionmentioning
confidence: 99%